Distinguish where the law does not distinguish. Bureaucratic practices and judicial action regarding the system of Family Allowances in prisons - Arcidiácono, Pilar (Universidad Nacional del Litoral, 2018)
Since 2009 Argentina has expanded the Family Allowances system with the creation of the Universal Child Allowance and also made changes and extensions in the traditional Assignments of the contributory field. However, a minority group that does not access these benefits will be analyzed here. It is the mothers who live with their children under 4 years of age in the context of confinement, a topic that reached the judicial seat and was granted a favorable ruling by the Chamber IV of the Criminal Cassation Chamber.